International collaborative research, systems leadership and education: reflections from academic biomedical researchers in Africa - Rose, Elizabeth S.; Bello-Manga, Halima; Boafor, Theodore; Asaduzzaman, Muhammad (Frontiers in Education, 2024)
Scope: Academic biomedical researchers and educators in African countries navigate complex local, national, and international systems to conduct grant-funded research. To secure funding, collaboration with researchers from high-income countries is often necessary. Existing literature highlights that these global health initiatives are commonly fraught with unequal power dynamics and lead by the foreign partners. Despite these inequalities, African faculty can benefit from these collaborations, fostering the development of their labs and careers. This study delves into reflections on lived experiences from academic biomedical researchers in Africa to better understand the impact of foreign collaborations.We designed a qualitative study using the Interpretative Phenomenological Analysis (IPA) method and used Self-determination and Complex Systems Leadership theories to frame this study. Ten academic biomedical researchers in Africa consented to join this study. The participants submitted a four-week series of reflective journals through an online data management platform. Subsequently, IPA methods were employed to analyze the collected journals. Results: Participants' reflections yielded six thematic key findings, encompassing their experiences in international collaborative research. The findings included: foreign dominance within the international macrosystem; resource challenges in their local microsystems; mesosystem dependency from collaborations; scholarly identity within research relationships; collaborative leadership; and the impact of the foreign perspective. From these findings, three implications were drawn suggesting that participants were 1) motivated by scholarly identity found in collaborations; 2) depended on collaborations that were colonialist but beneficial; and 3) created change through leadership at the microsystem level.Implications: Foreign collaborators and funders in global health education and research should critically consider how implications of this study relate to their collaborative work. Based on our analysis, recommendations for foreign collaborators and funders include prioritizing local leadership and perspectives in education initiatives and research grants; reviewing and leveraging collective leadership; engaging in bidirectional training, and mentoring opportunities; participating in power assessments; and removing publication barriers for researchers in Africa (and low-and middle-income countries). Insights from this study could impact global health research and education in multiple ways including new initiatives in mentorship and training in international collaborations along with increased awareness and correction of colonialism within these collaborations.